Special care dentistry: how prepared are we?. (20th November 2014) - Yeaton, S.; Moorthy, A.; Rice, J.; Coghlan, D.; O'Dwyer, L.; Green, E.; Sultan, A.; Guray, S.; Mohamad, N. A.; Aslam, N.; Freedman, L.
Abstract: Aim: To assess and evaluate the confidence of the undergraduate dental team in Irish dental schools regarding their training in the field of special care dentistry (SCD). Method: A questionnaire was distributed amongst the undergraduate dental teams within Cork University Dental School and Hospital (CUDSH) and Dublin Dental University Hospital (DDUH). The data were analysed to assess for differences between the median responses of the various groups. Results: A total of 139 students participated in the study; 82 from DDUH (59 dental science students, seven dental hygiene students and 16 dental nursing students) and 57 from CUDSH (43 dental science students and 14 dental hygiene students). Twenty‐two per cent ( n  = 30) of respondents agreed that their training had been sufficient in providing treatment or assistance for patients requiring SCD. Seventy‐five per cent agreed that more emphasis should be placed on clinical training in SCD ( n  = 76). Thirty‐one per cent of students anticipated a high level of confidence in treating patients requiring SCD upon graduation ( n  = 43), with dental science students feeling the least prepared amongst the dental team. Conclusion: Confidence levels of the undergraduate dental team were low with regard to SCD. The existing hands‐on clinical training in SCD was deemed insufficient by the respondents. Students believed more emphasis should be placed on SCD training in the undergraduate curriculum.